2024
DOI: 10.3390/v16020295
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Delta SARS-CoV-2 Infection on Glucose Metabolism: Insights on Host Metabolism and Virus Crosstalk in a Feline Model

Matthew T. Rochowski,
Kaushalya Jayathilake,
John-Michael Balcerak
et al.

Abstract: Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) causes enhanced mortality in people with metabolic and cardiovascular diseases. Other highly infectious RNA viruses have demonstrated dependence on glucose transport and utilization, so we hypothesized that SARS-CoV-2 infection could lead to alterations in cellular and whole-body glucose metabolism. Twenty-four healthy domestic cats were intratracheally inoculated with B.1.617.2 (delta) SARS-CoV-2 and samples were collected at 4- and 12-days post-ino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Other GLUTs, such as GLUT4, require activation by insulin to translocate from an intracellular vesicle to the cell surface in order to enable glucose diffusion into insulin-sensitive tissues. To the best of our knowledge, the protein expression of only a few GLUT isoforms have been reported in non-cancerous adult whole mammal lung (including rodents and humans) [5,19], although recent data have indicated that GLUT 1 and GLUT4 protein are also altered in the lung during SARS-CoV-2 infection in felines [20,21]. This study comprehensively evaluated both the gene and protein expression of the most predominant GLUT isoforms of Classes I and III in the lung of adult healthy mice in the same study.…”
Section: Discussionmentioning
confidence: 99%
“…Other GLUTs, such as GLUT4, require activation by insulin to translocate from an intracellular vesicle to the cell surface in order to enable glucose diffusion into insulin-sensitive tissues. To the best of our knowledge, the protein expression of only a few GLUT isoforms have been reported in non-cancerous adult whole mammal lung (including rodents and humans) [5,19], although recent data have indicated that GLUT 1 and GLUT4 protein are also altered in the lung during SARS-CoV-2 infection in felines [20,21]. This study comprehensively evaluated both the gene and protein expression of the most predominant GLUT isoforms of Classes I and III in the lung of adult healthy mice in the same study.…”
Section: Discussionmentioning
confidence: 99%